Trichilones A–E: New Limonoids from Trichilia adolfi - Mariela Gonzalez-Ramirez; Ivan Limachi; Sophie Manner; Juan C. Ticona; Efrain Salamanca; Alberto Gimenez; Olov Sterner (Molecules, 2021)
In addition to the trichilianones A–D recently reported from Trichilia adolfi, a continuing investigation of the chemical constituents of the ethanol extract of the bark of this medicinal plant yielded the five new limonoids 1–5. They are characterized by having four fused rings and are new examples of prieurianin-type limonoids, having a ε-lactone which in 4 and 5 is α, β- unsaturated. The structures of the isolated metabolites were determined by high field NMR spectroscopy and HR mass spectrometry. The new metabolites were shown to have the ε-lactone fused with a tetrahydrofuran ring which is connected to an oxidized hexane ring joined with a cyclo-pentanone having a 3-furanyl substituent. As the crude extract possesses antileishmanial activity, the compounds were assayed for cytotoxic and antiparasitic activities in vitro in murine macrophage cells (raw 264.7 cells) and in Leishmania amazoniensis as well as L. braziliensis promastigotes. Metabolites 1–3 and 5 showed moderate cytotoxicity (between 30–94 µg/mL) but are not responsible for the antileishmanial effect of the extract.